Penguatan Multikulturalisme Menyongsong Ibu Kota Negara (IKN) Kajian Seni Rupa Kalimantan Timur era 2020-an - Citra Smara Dewi (Journal of Contemporary Indonesian Art, 2023)
This study will focus on the development of East Kalimantan's fine arts, especially in dealing with the State Capital (IKN). One important aspect in building IKN is strengthening the values of multiculturalism as a cultural foundation. This study will focus on the works of East Kalimantan painters, which were created in 2022, through the Cloning Art Exhibition, Balikpapan 2022. This exhibition is very important because it represents the development of modern-contemporary art in East Kalimantan in the 2020s era, which emphasizes local potential both in the context of selecting themes with the spirit of glocalization and also the movement of dynamic expression. Studying the works of East Kalimantan Fine Arts is very important in an effort to identify the various potentials as well as obstacles faced by artists in facing IKN. The previous study was the Study of the Archipelago Art Exhibition, at GNI, Jakarta, 2001 – 2017. The novelty in this study, is more specifically to examine the works of art in East Kalimantan through an exhibition initiated by the local community in 2022. The spirit of ethnosymbolism becomes its own strength of works created by East Kalimantan artists. The method used is a historical approach: Heuristics, Criticism, Interpretation and Historiography, with material culture analysis. The results of the study show that cultural elements, such as symbols, mythology, memory, values, rituals, and traditions as the spirit of multiculturalism are seen in the works of East Kalimantan artists.Kajian ini berfokus pada perkembangan seni rupa Kalimantan Timur, khususnya dalam menghadapi Ibu Kota Negara (IKN). Salah satu aspek penting dalam membangun IKN adalah penguatan nilai-nilai multikulturalisme sebagai landasan kultural Kajian ini berfokus pada karya-karya pelukis Kalimantan Timur, yang diciptakan pada tahun 2022, melalui Pameran Cloning Art Exhibition, Balikpapan 2022.  Pameran ini menjadi sangat penting karena merupakan representasi perkembangan seni rupa modern-kontemporer Kalimantan Timur era 2020-an, yang mengedepankan potensi kelokalan baik dalam konteks pemilihan tema-tema dengan spirit glokalisasi dan juga gerak ekspresi dinamis. Mengkaji karya-karya Seni Rupa Kalimantan Timur, menjadi sangat penting dalam upaya menemukenali berbagai potensi sekaligus hambatan yang dihadapi seniman dalam menyongsong IKN. Kajian sebelumnya sebelumnya Kajian Tentang Pameran Seni Rupa Nusantara, di GNI,  Jakarta, Tahun 2001 – 2017. Kebaruan pada kajian ini, lebih spesifik mengkaji karya-karya seni rupa Kalimantan Timur melalui pameran yang digagas komunitas lokal pada tahun 2022. Semangat Etnosimbolisme menjadi kekuatan tersendiri dari karya-karya diciptakan seniman Kalimantan Timur. Metode yang digunakan yaitu pendekatan sejarah : Heuristik, Kritik, Interpretasi dan Historiografi, dengan analisis material culture. Hasil kajian menunjukan bahwa elemen budaya, seperti simbol, mitologi, ingatan, nilai, ritual, dan tradisi sebagai spirit Multikulturalisme terlihat pada karya-karya perupa Kalimantan Timur.